Preparation and characterization of activated palm kernel shell/carboxylated nitrile butadiene rubber (APKS/XNBR) vulcanizate / Syazwani Aqilah Zainal ... [et al.] - Zainal, Syazwani Aqilah; Mamauod, Siti Nur Liyana; Zainal, Nahrul Hayawin; Ismail, Hanafi; Mamauod, Muhammad Ilham (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2024)
Malaysia is one of the most important palm oil producers and exporters in the whole wide world. There has been a rapid development of new palm oil plantations and palm oil mills in this country. The palm oil industry plays a vital role in the economic growth of Malaysia. However, as the palm oil industry grows bigger and wider, a huge amount of palm oil waste is produced which is an alarming issue considering it can cause pollution and have a negative effect on the environment. Raw Palm Kernel Shell (PKS) derived from palm oil waste can be converted into Activated Palm Kernel Shell (APKS) which has the potential to be a value-added biofiller in rubber vulcanizates. Thus, in this study, APKS is prepared through a carbonization process at a temperature of 900 °C and an activation process via steam treatment and used as filler in Carboxylated Nitrile Butadiene Rubber (XNBR). The aim of this study is to evaluate the influence of different loading ratios of APKS on the swelling index measurement, bound rubber content (BRC), abrasion resistance, compression set, and hardness of XNBR vulcanizates. APKS is incorporated in XNBR at different loading ratios, ranging from 0 to 50 phr and these APKS-filled XNBR vulcanizates are prepared with a two-roll mill. The overall physico-mechanical properties of APKS-filled XNBR vulcanizates showed increment in terms of BRC, compression set, and hardness as the loading ratio of APKS increased. XNBR vulcanizates with a higher loading ratio of APKS also showed a decrease in swelling index measurement and volume loss which would indicate high abrasion resistance. These results could be attributed to the porosity of APKS as shown in the morphological analysis which provided a high surface area of contact for crosslinking and mechanical interlocking. This proves APKS could potentially be a semi-reinforcing filler for rubber vulcanizates, especially for XNBR vulcanizates as XNBR vulcanizates were able to achieve high abrasion resistance and high hardness with the incorporation of APKS. With this, the conversion of PKS into APKS could help to reduce palm oil waste and provide an environmentally friendly, sustainable biofiller option to rubber researchers and manufacturers who are looking for an alternative to petroleum-based fillers. This would be very beneficial for both the palm oil industry and the rubber industry.